The impact of lesion location on dysphagia incidence, pattern and complications in acute stroke. Part 1: dysphagia incidence, severity and aspiration - Suntrup, S.; Kemmling, A.; Warnecke, T.; Hamacher, C.; Oelenberg, S.; Niederstadt, T.; Heindel, W.; Wiendl, H.; Dziewas, R. (European journal of neurology, 2015)
Background and purpose Although early identification of patients at risk for dysphagia is crucial in acute stroke care, predicting whether a particular patient is likely to have swallowing problems based on the brain scan is difficult because a comprehensive model of swallowing control is missing. In this study whether stroke location is associated with dysphagia incidence, severity and the occurrence of penetration or aspiration was systematically evaluated relying on a voxel‐based imaging analysis approach. Methods Two hundred acute stroke patients were investigated applying fiberoptic endoscopic evaluation of swallowing within 96 h from admission. Lesion masks were obtained from each patient's brain scan and registered to standard space. The percentage of lesioned volume of 137 atlas‐based brain regions was determined in each case. Region‐specific odds ratios were afterwards calculated with respect to presence of dysphagia, its severity and occurrence of penetration or aspiration. Results In all, 165 patients were diagnosed with dysphagia, 80 of whom had severe swallow impairment. For each investigated item there were significant differences of regional percentage infarction in distinct brain areas between affected patients and those who did not present with that specific dysfunction. In particular, right hemispheric lesions of the pre‐ and post‐central gyri, opercular region, supramarginal gyrus and respective subcortical white matter tracts were related to dysphagia, with post‐central lesions being especially associated with severe swallowing impairment. Conclusions Distinct brain lesion locations are related to the incidence, severity and pattern of swallowing dysfunction.